Deep Sequencing Analysis of Human T Cell Lymphotropic Virus Type 1 Long Terminal Repeat 5' Region from Patients with Tropical Spastic Paraparesis/Human T Cell Lymphotropic Virus Type 1-Associated Myelopathy and Asymptomatic Carriers - Rego, Filipe Ferreira de Almeida; de Oliveira, Tulio; Giovanetti, Marta; Galvão-Castro, Bernardo; Gonçalves, Marilda de Souza; Alcantara, Luiz Carlos (AIDS research and human retroviruses, 2016)
The aim of this study was to analyze patients by deep sequencing the human T cell lymphotropic virus type 1 (HTLV-1) long terminal repeat (LTR) region in order to determine if minor and/or major mutations in this promoter region might be associated with tropical spastic paraparesis (TSP)/human T cell lymphotropic virus type 1-associated myelopathy (HAM) outcome or proviral load or HTLV-1 expression. This study is a cross-sectional analyze of 29 HTLV-1-infected patients with TSP/HAM or asymptomatic carriers. Proviral DNA from those subjects was submitted to a nested PCR for the HTLV-1 LTR5' region. The HTLV-1 LTR5' purified products were submitted to deep sequencing using the Ion Torrent sequencing technology (Life Technologies, Carlsbad, CA). We found that samples with low proviral load showed more detected minor mutations than the samples with high proviral load. Mutations in 136 positions were found over the 520-bp analyzed fragment of HTLV-1 LTR5' with at least 1% frequency. Eleven mutations were present in the previously determined major transcription factor binding sites (TFBS) and in more than one patient, indicating that there might be a differential HTLV-1 expression comparing individuals or in comparing different cells from the same individual. Three mutations were statistically significant using the Fisher nonparametric test between the groups but were not present in previously determined TFBS (G126C/T, G306C, and C479T). Those mutations that were not present in previously determined TFBS were statistically significant in this study and were most frequent in patients with low proviral load or in asymptomatic carriers. Although those mutations were not present in previously determined TFBS, one of those mutations (G306C/A) was present in an Sp-1 binding site determined by in silico analysis, and its presence abrogated the site for Sp-1 binding and created a new possible ATF binding site.